Bringing phonological oddities to the fore: The Basque sibilants - Igartua, Iván (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2025)
The contrast between apical and laminal articulations in Basque dento-alveolar sibilant consonants has traditionally attracted linguists’ attention. This distributedness distinction, as it has come to be known in the literature, was assumed to be very uncommon, a sort of typological oddity (perhaps the only one) of Basque consonantism, which, in all other respects, is not particularly remarkable in terms of its phonological characteristics. Many studies have been devoted to the articulatory and acoustic properties of sibilants in Standard Basque and several dialectal varieties. In this paper, written as a contribution to this well-deserved Festschrift in honor of José Ignacio Hualde, I compare the Basque system of sibilants and its features with other structurally more or less analogous systems, drawing on recent typological research, in order to gain a more nuanced understanding of the alleged uniqueness of the Basque sibilants.